2020
DOI: 10.3390/nu12072072
|View full text |Cite
|
Sign up to set email alerts
|

An Infant Formula with Partially Hydrolyzed Whey Protein Supports Adequate Growth and Is Safe and Well-Tolerated in Healthy, Term Infants: A Randomized, Double-Blind, Equivalence Trial

Abstract: The current study evaluates the safety and tolerance of a partially hydrolyzed whey protein-based infant formula (PHF) versus an in intact cow’s milk protein formula (IPF). Breastfed infants were included as a reference group. In a multi-country, multicenter, randomized, double-blinded, controlled clinical trial, infants whose mothers intended to fully formula feed were randomized to PHF (n = 134) or IPF (n = 134) from ≤14 days to 17 weeks of age. The equivalence analysis of weight gain per day within margins … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

12
15
0
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 15 publications
(29 citation statements)
references
References 33 publications
12
15
0
2
Order By: Relevance
“…The analysis of the primary objective was achieved by demonstrating the equivalence in daily weight gain from baseline to 17 weeks of age in infants receiving the Test compared to the Control IF. In addition, the mean (SE) values of daily weight gain 31.00 (0.59) g/day and 31.08 (0.60) g/day in the Test and Control group in the current study are in line with previously published data from other studies evaluating IF [24,25,31]. We have previously reported a mean (SD) daily weight gain of 28.3 (7.4) g/day and 30.1 (6.6) g/day for infants fed a partly fermented formula with scGOS and lcFOS or a non-fermented IF without scGOS and lcFOS until 17 weeks of age [24].…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…The analysis of the primary objective was achieved by demonstrating the equivalence in daily weight gain from baseline to 17 weeks of age in infants receiving the Test compared to the Control IF. In addition, the mean (SE) values of daily weight gain 31.00 (0.59) g/day and 31.08 (0.60) g/day in the Test and Control group in the current study are in line with previously published data from other studies evaluating IF [24,25,31]. We have previously reported a mean (SD) daily weight gain of 28.3 (7.4) g/day and 30.1 (6.6) g/day for infants fed a partly fermented formula with scGOS and lcFOS or a non-fermented IF without scGOS and lcFOS until 17 weeks of age [24].…”
Section: Discussionsupporting
confidence: 92%
“…We did, however, demonstrate equivalence in both length and head circumference gain between these groups during the intervention. The observed weight gain value of the breastfed infants in the current study is close to the range of values previously reported for breastfed infants (26.8–30.3 g/day up to four months of age) [ 24 , 31 , 32 , 33 ]. Given the high similarity in weight gain velocity between both IF groups, we did not evaluate the equivalence between the Control group and the Breastfed reference group.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…First and foremost, similar results were found in the study by Karaglani et al, which assessed the effects on growth parameters of a pHF compared to an IPF in 163 healthy formula-fed infants over a period of three months (19). Similarly, other previous studies investigating the effects of different pHFs on growth indices of infants as compared to intact protein-based formulas or breast milk have found no differences among the study groups (20)(21)(22)(23). Moreover, during the 10-year follow-up of the German Infant Nutritional Intervention Study (GINI) no differences were observed in weight, length and BMI gains of infants with atopic heredity fed with either a partially hydrolysed formula, an extensively hydrolysed formula, a cow's-milk based formula or breast milk (24,25).…”
Section: Discussionsupporting
confidence: 77%
“…Moreover, “predigested” IFs seem to induce a better feeding tolerance for preterm infants, which was indicated by higher gastrointestinal transport rates, more rapid gastric emptying, less gastro-esophageal reflux, and more rapid establishment of full enteral feeding [ 5 ]. More recently, an IF with partially hydrolyzed WP was proved to support adequate growth for healthy term infants [ 6 ]. WP hydrolysate was also found to serve as a probiotic growth and metabolism enhancer for Wistar rats, which were fed with a standard diet [ 7 ].…”
Section: Introductionmentioning
confidence: 99%